The Influence of Gamma-rays on the Injury and Chromosomal Aberrations of Long Bean (Vigna sesquipedalis, Fruw.) - C., Mak; Teoh, S. B.; Ratnam, A. (1986)
The effects of gamma-rays on three varieties of long bean (Vigna sesquipedalis, Fruw), namely Melaka, Local Black and Local Long were studied using Jive doses ranging from 10 to 50 kR. Both Chromosomal aberrations and characteristics related to physiological damage were used to study radiation sensitivity of the varieties. In general, gamma radiation did not affect % seed germination but caused a significant reduction in characteristics related to survival, growth and fertility. Percentage chromosomal aberrations also increased with increasing dose. As the measurement of seedling height is simple, quick and highly correlated with most characteristics studied, it could be a useful parameter in the study of radiation effects on long bean. Using a critenrion of approximately 30% reduction in seedling height or 50% lethality, it is suggested that doses ranging from 30 to 50 kR would be suitable for mutation induction in long bean.